Decentralized humanitarian aid deployment: reimagining the delivery of aid - Erik Xavier Wood; Tim Frazier (Journal of Humanitarian Logistics and Supply Chain Management)
Purpose – Current centralized humanitarian aid deployment practices may encourage urbanization thereby weakening short- and long-term resiliency of lower-income countries receiving aid. The purpose of this paper is first, to explore these shortcomings within the peer-reviewed literature and, second, propose a starting point for a solution with a decentralized humanitarian aid deployment (DHAD) framework. Design/methodology/approach – The authors conducted a focused, qualitative review of available and relevant literature. Findings – The literature reviewed demonstrates that current centralized humanitarian aid deployment models lack meaningful engagement of local assets while indicating a plausible connection between these same models and disaster urbanization. Next, the literature shows introducing a new decentralized model could represent a sustainable aid deployment standard for that country’s specific response, recovery, mitigation and planning opportunities and constraints. Research limitations/implications – The next step is to develop a working DHAD model for a lower-income country using a multi-layered, GIS analysis that incorporates some or all of the socioeconomic and environmental variables suggested herein. Practical implications – The practical potential of the DHAD framework includes establishing the impacted country in the lead role of their own recovery at the moment of deployment, no longer relying on foreign logistics models to sort it out once aid has arrived. Originality/value – This paper discusses a topic that much of the literature agrees requires more research while suggesting a new conceptual framework for aid deployment best practices which is also largely absent from the literature.